Grain-boundary segregation and precipitates in La2O3 and Pr2O3 doped SnO2 center dot CoO-based varistors - Oliveira, M. M.; Soares, P. C.; Bueno, Paulo Roberto [UNESP]; Leite, E. R.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Elsevier B.V., 2003)
Structural heterogeneities in SnO2.CoO-based varistors were analyzed by transmission electron microscopy. In SnO2.CoO-based system doped with La2O3 and Pr2O3 two kinds of precipitate phases at grain boundary region were found. Using energy dispersive spectrometry they were found to be Co2SnO4 and Pr2Sn2O7, presenting a defined crystalline structure. It was also identified that such precipitate phases are mainly located in triple-junctions of the microstructure. HRTEM analysis revealed the existence of other two types of junctions, one as being homo-junctions of SnO2 grains and other due to twin grain boundaries inside the SnO2.CoO grain. The role of these types of junction in the overall nonlinear electrical features is also discussed. (C) 2003 Elsevier B.V. Ltd. All rights reserved.
Keywords: CoO; grain boundaries; microstructure-final; SnO2; varistors